PERAN PRAKTIK HUMAN RESOURCE MANAGEMENT TERHADAP RETENSI KARYAWAN: SUPPORTIVE WORK ENVIRONMENT SEBAGAI MEDIATOR - Febriyanti, Berliana Uci; Wulandari, Fitri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.04.TAHUN.2025DO - 10.24843/EEB.2025.v14.i04.p07, 2025)
Employees are valuable assets for companies, making their retention a key challenge in human resource management (HRM). This study analyzes the impact of HRM practices on employee retention, with Supportive Work Environment (SWE) as a mediating factor, using data from 138 respondents across various companies in Indonesia. The data was analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that compensation has a significant positive effect on SWE (coefficient 0.291; p = 0.017) and employee retention (coefficient 0.384; p = 0.000). Performance appraisal also positively influences SWE (coefficient 0.512; p = 0.000) and employee retention (coefficient 0.290; p = 0.001). Furthermore, SWE has a positive impact on employee retention (coefficient 0.310; p = 0.002). However, training and development do not show a significant effect on SWE (coefficient 0.128; p = 0.367). These findings support Social Exchange Theory (SET), which explains that employees tend to demonstrate greater loyalty when they feel valued through fair compensation and transparent performance evaluation systems. This study highlights the importance of HRM policies focusing on compensation and performance appraisal to enhance employee retention, while also emphasizing the need for further evaluation of training and development programs in fostering a supportive work environment.